Megafauna large-scale distribution patterns along the Gloria Fracture Zone (NE Atlantic) - Ferreira, Teresa Regina Cardoso (2022)
As falhas cobrem extensas áreas de fundos marinhos e estão associadas a paisagens e contextos ambientais complexos. Neste estudo foram utilizadas imagens capturadas em quatro áreas para caracterizar a mega-epifauna bentónica ao longo da falha Gloria e os resultados foram explorados considerando a variação ambiental. As variáveis ambientais investigadas revelaram similaridade entre o segmento ocidental e central. Nestas áreas, as densidades de mega-epifauna foram menores, mas a composição variou devido a diferenças entre proporções de Anthozoa e Holothuroidea. Pelo contrário, no segmento oriental foram observadas as maiores densidades e maiores proporções de Anthozoa. O rift da Terceira apresentou uma das maiores densidades e constituiu uma das áreas mais diversas, possivelmente devido á maior produtividade e variedade de substrato observada. Este estudo apresenta pela primeira vez resultados referentes aos padrões de distribuição e diversidade de fauna abissal ao longo da falha Gloria, com relevância para a futura gestão e conservação, inclusivamente de áreas de jurisdição nacional; ABSTRACT: Megafauna large-scale distribution patterns along the Gloria Fracture Zone (NE Atlantic) Faults are extensive seafloor features associated with large-scale landscape and environmental complexity. This study focused on the characterization of benthic mega-epifaunal assemblages explored in relation to environmental setting, using imagery surveys carried along four areas of the Gloria Fault. The environmental variables investigated revealed similarity between western and central segments of the Gloria Fault. In these two areas lower densities were observed, but composition showed variability, due to different proportions of Anthozoa and Holothuroidea. By opposition, the highest total density was observed at the eastern segment, where high proportions of Anthozoa were observed. The Terceira rift area was characterised by high densities and high diversity, possibly associated to higher productivity and a more diverse substrata composition. This study reports for the first-time on the spatial distribution patterns and diversity of abyssal fauna of the Gloria Fault, including in areas under national jurisdiction, with relevance for future management and conservation actions.